OPTIMIZATION OF METHODS FOR PREPARATION OF RECOMBINANT TOBACCO ETCH VIRUS PROTEASE FROM Escherichia coli cells - A. V. Ryabchenko; M. V. Kotova; R. A. Knyazev; N. V. Trifonova; L. M. Polyakov (Сибирский научный медицинский журнал, 2019)
The catalytic domain of the nuclear inclusion protein of the tobacco etch virus protease, TEVp, is used for the cleavage of artificial fusion polypeptides. However, the production of a recombinant enzyme has certain difficulties, such as a low yield of the product and its low solubility in physiological solutions. The aim of the study was to optimize the methods of producing a recombinant enzyme TEVp from E. coli producing cells. Material and methods. The studies were carried out on E. coli cells st. BL21 (DE3). The enzyme was synthesized by cells in the form of a fusion polypeptide with maltose-binding protein (MBP), followed by self-cleavage. Biomass production was carried out under various conditions: a change in the temperature regime, the time of incubation of cells with an inducer, the concentration of the inducer and the growth phase of the culture with the addition of an inducer. The enzyme was isolated under native conditions and with an increased concentration of sodium chloride by affinity chromatography. The enzyme activity was tested on chimeric recombinant human apolipoprotein A-I (~33.4 kDa). Results and discussion. The results of the study showed that a significant influence on the final yield of the enzyme was provided by the growth phase of the culture when the inducer was added. Optimal conditions for obtaining biomass were found as follows: incubation temperature with an inducer 30 °C; incubation time 4 hours; inducer concentration 200 μM; optical density with inducer addition 2.0-2.5 optical units per ml. Sodium chloride concentration in the buffer solution during isolation of the protein was 150 mM. The yield of the enzyme under these conditions reached 50 mg from a liter of cell culture. A similar yield of the enzyme was obtained using the method of auto-induction of cell culture. In all cases, enzymes retained their activity. Conclusion. It was shown that the greatest influence on the yield of the recombinant enzyme from E. coli producing cells strain BL21 (DE3) in the expression vector pD441-MBP under the regulation of the bacteriophage promoter gene «T5» was exerted by the growth phase of the cell culture at the time of gene expression launch.